Dose-Dependent Effects of Zoledronic Acid on Human Periodontal Ligament Stem Cells: An In Vitro Pilot Study. (20th October 2020) - Di Vito, Anna; Chiarella, E.; Baudi, F.; Scardamaglia, P.; Antonelli, A.; Giudice, D.; Barni, T.; Fortunato, L.; Giudice, A.
Bisphosphonates (BPs) are widely used to treat several metabolic and oncological diseases affecting the skeletal system. Despite BPs' well-known therapeutic potential, they also displayed important side effects, among which is BPs-related osteonecrosis of the jaw, by targeting osteoclast activities, osteoblast, and osteocyte behavior. The aim of this study is to evaluate the biological effects of zoledronic acid (ZOL) in an in vitro model of periodontal ligament stem cells (PDLSCs) by using an experimental setting that resembles the in vivo conditions. PDLSCs were treated with different concentrations of ZOL ranging from 0.1 to 5 μM. The effects of ZOL exposure were evaluated on cell viability via 3-[4, 5-Dimethylthiaoly]-2, 5-diphenyltetrazolium bromide (MTT), cell cycle analysis, apoptosis detection, and immunofluorescence. Quantitative real-time polymerase chain reaction (PCR), colorimetric detection of alkaline phosphatase activity, and Alizarin Red S staining were performed to investigate the osteogenic potential of PDLSCs exposed to ZOL. MTT analysis showed that the viability of PDLSCs exposed to ZOL concentration ≥1.5 μM for 3 and 6 days was significantly lower ( P < 0.001) than that of untreated cells. The percentage of apoptotic cells was significantly higher in PDLSCs exposed for 4 days to ZOL at 2 μM ( P < 0.01) and 5 μM ( P < 0.001) when compared to the control. Moreover, ZOL treatment (3 days) accounted for alterations in cell cycle distribution, with an increase in the proportion of cells in G0/G1 phase and a reduction in the proportion of cells in S phase. Chronic exposure (longer than 7 days) of PDLSCs to ZOL accounted for the downregulation of ALP, RUNX2, and COL1 genes at all tested concentrations, which fit well with the reduced alkaline phosphatase activity reported after 7 and 14 days of treatment. Reduced Col1 deposition in the extracellular matrix was reported after 14 days of treatment. Increased calcium deposits were observed in treated cells when compared to the control cultures. In conclusion, chronic exposure to 1 μM ZOL induced significant reduction of osteogenic differentiation, while ZOL concentrations ≥1.5 μM are required to impair PDLSCs viability and induce apoptosis.